Chapter 4. Morphology: Nouns - Nesset, Tore (Septentrio Educational, 2015)
Learning Contemporary Standard Russian, you have struggled with all the exceptions from the rules. Where do the exceptional inflections of words such as время ‘time’, телёнок ‘calf’ and дочь ‘daughter’ come from? Why is путь the only masculine noun in declension III? Why do some masculines such as рог ‘antler’ and глаз ‘eye’ have ‑a, and not ‑ы in the nominative plural? And where do exceptional plural forms such as небеса and чудеса from небо ‘heaven’ and чудо ‘wonder’ come from? This chapter offers answers to these and many other questions. We start from what you are already familiar with, namely nouns in Contemporary Standard Russian (section 4.1), and then turn to changes concerning declension classes (4.2 and 4.3), number and case (4.4), hard and soft stems (4.5), gender (4.6), and animacy (4.7). You find a brief summary in section 4.8. Download the video to learn more.